The impact of multiple non-pharmaceutical interventions for China-bound travel on domestic COVID-19 outbreaks - Yang, Lichao; Hu, Mengzhi; Zeng, Huatang; Liang, Wannian; Zhu, Jiming (Frontiers in Public Health, 2023)
Objectives: Non-pharmaceutical interventions (NPIs) implemented on China-bound travel have successfully mitigated cross-regional transmission of COVID-19 but made the country face ripple effects. Thus, adjusting these interventions to reduce interruptions to individuals’ daily life while minimizing transmission risk was urgent. Methods: An improved Susceptible-Infected-Recovered (SIR) model was built to evaluate the Delta variant's epidemiological characteristics and the impact of NPIs. To explore the risk associated with inbound travelers and the occurrence of domestic traceable outbreaks, we developed an association parameter that combined inbound traveler counts with a time-varying initial value. In addition, multiple time-varying functions were used to model changes in NPIs implementation. Related parameters of functions were ran by the MCSS method with 1000 iterations to derive the probability distribution. Initial values, estimated parameters and corresponding 95% CI were obtained. Reported existing symptomatic, suspected, and asymptomatic case counts were used as the training datasets. Reported cumulative recovered individual data was used to verify the reliability of relevant parameters. Lastly, we used the value of ratio (Bias^2/Variance) to verify the stability of mathematic model, and the effects of the NPIs on the infected cases to analyze the sensitivity of input parameters. Results: The quantitative findings indicated that this improved model was highly compatible with publicly reported data collected from July 21 to August 30, 2021. The number of inbound travelers was associated with the occurrence of domestic outbreaks. A proportional relationship between Delta variant incubation period and PCR test validity period was found. The model also predicted that restoration of pre-pandemic travel schedules while adhering to NPIs requirements would cause shortages in health resources. The maximum demand for hospital beds would reach 25,000/day, the volume of PCR tests would be 8,000/day, and the number of isolation rooms would reach 800,000/day within 30 days. Conclusions: With the pandemic approaching the end, reexamining it carefully helps better address future outbreaks. This predictive model has provided scientific evidence for NPIs’ effectiveness and quantifiable evidence of health resource allocation. It could guide the design of future epidemic prevention and control policies, and provide strategic recommendations on scarce health resource allocation.